Analisis konstruksi sosiologis Yohanes 4 tentang religiositas Yesus - Siahaya, Karel Martinus; Warella, Sipora Blandina; Daud, Yulius (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
Social injustice has been exposed to the surface which results in communities that do not prosper together. It is said that they are not prosperous together, considering that the strong social class is in a condition that remains prosperous while the weak ones remain in a state of not prosperity, while both the strong and weak social classes are compatriots who are bound by regulations rooted in Yahweh which want justice and prosperity to be upheld. In other words, a good community character is wanted to be achieved, namely the character of a community that does not like the existence or strengthens conditions of poverty and injustice. The development of social and economic conditions in Israel changed when social classes were formed. The socio-economic structure that was created bringing the problems of poverty began to strengthen in reality. It is predicted not because of the financial economy that was not visible in later Israeli life, for the side-by-side resilience of a financial economic system and a principal of the barter system or the exchange of goods while in Palestine at its inception. But a change in social and economic structure in Israel since the period of the kingdom which experienced rapid development, including increasing state taxes, is burdening the economic life of the rural peasants. This condition felt the need for economic liberation.